Anticonvulsant activity of Caryocar coriaceum Wittm. fixed pulp oil against pentylenetetrazol-induced seizures. (3rd August 2017) - Oliveira, Cleide Correia; Oliveira, Clarissa Vasconcelos; Grigoletto, Jéssica; Ribeiro, Leandro Rodrigo; Funck, Vinícius Rafael; Meier, Letícia; Fighera, Michele Rechia; Royes, Luiz Fernando Freire; Furian, Ana Flávia; Menezes, Irwin Rose Alencar; Oliveira, Mauro Schneider
Abstract: Objectives: Epilepsy is a common brain disease and a major worldwide public health problem. The seizures in a significant number of patients suffering from epilepsy remain inadequately controlled by currently available pharmacological treatments. Accordingly, there is a need for the discovery of new anticonvulsant approaches with improved efficacy and a better safety profile. In this context, natural products can be a valuable source of substances with potential anticonvulsant activity. In the present study, we tested the anticonvulsant potential of Caryocar coriaceum Wittm., a plant native from the Brazilian Cerrado biome (tropical savanna ecoregion). Methods: Adult male C57BL/6 mice were treated with increasing doses of the fixed oil obtained from the pulp of Caryocar coriaceum Wittm. Seizure activity was induced by PTZ (60 mg/kg, i.p.), and evaluated by behavioral and electrographic methods. Potential adverse effects were investigated in the open-field, rotarod, forced swim, or object recognition tests. The antioxidant potential of the oil was evaluated by the DPPH scavenging assay. Results: Administration of the oil at the dose of 100 mg/kg increased the latency for the first myoclonic jerk and the first generalized tonic–clonic seizures. The duration of generalized convulsions induced by PTZ was not altered. No significant behavioral adverse effects were detected in the open-field, rotarod, forced swim, or object recognition tests. Interestingly, a significant antioxidant activity of Caryocar coriaceum Wittm. fixed pulp oil was detected in the DPPH scavenging assay. Discussion: Natural products can be a valuable source of substances with potential anticonvulsant activity and improved safety profile. Further studies are needed to evaluate the mechanisms underlying the anticonvulsant effects of Caryocar coriaceum Wittm. fixed pulp oil as well as the potential of the oil as a source of new anticonvulsant compounds.